Dystocia due to Dicephalus monstomus monster in a crossbred cow - CHANDRAHASAN, C; KUMAR, K KRISHNA; SELVARAJU, M; RICHARD, P N; JAGATHEESAN,; SARAVANA KUMAR, V RAMESH (The Indian Journal of Animal Reproduction, 2023)
Dystocia due to dicephalus monstomus monster has been reported in a crossbred cow.
Keywords: Dystocia; pregnant; monster